Effect of Compensation and Organizational Commitment on Employee Performance During WFH at Digital Company - Ahmad Azmy (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractThis study discusses the effect of compensation and organizational commitment on the performance of employees working from home during the COVID-19 pandemic. The object of the study was a digital platform-based outsourcing company. Research respondents were employees who work in digital platform-based outsourcing companies. The sampling technique used was a stratified approach by making criteria according to research needs. The method used is Partial Least Square. The data were obtained from a total of 100 respondents. The results showed that compensation and organizational commitment had a significant effect on employee performance. Compensation shows how employees still need financial resources that must be paid on time by the company. Organizational commitment shows the company's support while working from home during the COVID-19 pandemic. The company provides support for access to technology and resources to ensure maximum performance achievement by employees. This study provides recommendations to improve compensation for optimalization performance.Keywords: Compensation, Organizational Commitment, Work from Home, Employee PerformancePengaruh Kompensasi dan Komitmen Organisasi terhadap Kinerja Karyawan Selama Bekerja dari Rumah pada Perusahaan Digital OutsourcingAbstrakPenelitian ini membahas tentang pengaruh kompensasi dan komitmen organisasi terhadap kinerja karyawan yang bekerja dari rumah selama masa pandemi COVID-19. Objek penelitian dilakukan pada perusahaan outsourcing berbasis platform digital. Responden penelitian adalah karyawan yang bekerja di perusahaan outsourcing berbasis platform digital. Teknik pengambilan sampel menggunakan pendekatan stratified dengan membuat kriteria sesuai kebutuhan penelitian. Metode yang digunakan adalah Partial Least Square. Jumlah data yang digunakan adalah 100 responden. Hasil penelitian menunjukkan bahwa kompensasi dan komitmen organisasi berpengaruh signifikan terhadap kinerja karyawan. Kompensasi menunjukkan bagaimana karyawan masih membutuhkan sumber daya keuangan yang harus dibayar tepat waktu oleh perusahaan. Komitmen organisasi menunjukkan dukungan perusahaan selama bekerja dari rumah selama pandemi COVID-19. Perusahaan memberikan dukungan akses teknologi dan sumber daya untuk memastikan pencapaian kinerja yang maksimal oleh karyawan. Penelitian ini memberikan rekomendasi kepada perusahaan untuk memperhatikan kompensasi dan komitmen organisasi untuk menjamin efektivitas pencapaian kinerja. Kata kunci: Kompensasi, Komitmen Organisasi, Bekerja dari Rumah, Kinerja Karyawan